2018
DOI: 10.1292/jvms.17-0680
|View full text |Cite
|
Sign up to set email alerts
|

The first report of terbinafine resistance <i>Microsporum canis</i> from a cat

Abstract: A 2-year-old, exotic shorthair cat presented with baldness and mild scaling on trunk that was confirmed as Microsporum canis (M. canis) infection by the following methods. Wood’s lamp and trichogram were used to demonstrate fungal elements suggestive of dermatophytosis consistent with M. canis. Dermatophyte test medium (DTM) and polymerase chain reaction (PCR) were used for identification. E-test and broth microdilution test were then utilized to estimate antifungal minimal inhibitory concentrations (MICs) tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 6 publications
1
21
0
2
Order By: Relevance
“…Interestingly, we found that two animal isolates and one human isolate responded to terbinafine at high MICs (4‐8 and 4 μg/mL, respectively), which is, however, consistent with previous studies reporting high MICs of terbinafine for M. canis clinical isolates. A terbinafine‐resistant M. canis strain (MIC > 32 μg/mL) was obtained from a short‐hair cat, which was then treated with systemic itraconazole, and M. canis isolates responding to high MICs (4 and 8 μg/mL) of terbinafine were found to be associated with human infections . In this study, the MIC range for itraconazole against M. canis isolates (0.001‐2 μg/mL) was the same as that reported before; similar itraconazole MICs of ≤1 μg/mL were also observed for M. canis strains in other studies .…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Interestingly, we found that two animal isolates and one human isolate responded to terbinafine at high MICs (4‐8 and 4 μg/mL, respectively), which is, however, consistent with previous studies reporting high MICs of terbinafine for M. canis clinical isolates. A terbinafine‐resistant M. canis strain (MIC > 32 μg/mL) was obtained from a short‐hair cat, which was then treated with systemic itraconazole, and M. canis isolates responding to high MICs (4 and 8 μg/mL) of terbinafine were found to be associated with human infections . In this study, the MIC range for itraconazole against M. canis isolates (0.001‐2 μg/mL) was the same as that reported before; similar itraconazole MICs of ≤1 μg/mL were also observed for M. canis strains in other studies .…”
Section: Discussionsupporting
confidence: 75%
“…32 Interestingly, we found that two animal isolates and one human isolate responded to terbinafine at high MICs (4-8 and 4 μg/mL, respectively), which is, however, consistent with previous studies reporting high MICs of terbinafine for M. canis clinical isolates. A terbinafine-resistant M. canis strain (MIC > 32 μg/mL) was obtained from a shorthair cat, which was then treated with systemic itraconazole, 16 and M.…”
Section: Me Thodsmentioning
confidence: 99%
See 3 more Smart Citations